The effect of mobile element IS10 on experimental regulatory evolution in Escherichia coli - DORMAN, CHARLES (My University, 2010)
Mobile genetic elements are widespread in bacteria, where they cause several kinds of mutations. Although their effects are on the whole negative, rare beneficial mutations caused by insertion sequence elements are frequently selected in some experimental evolution systems. For example, in earlier work, we found that strains of Escherichia coli that lack the sigma factor RpoS adapt to a high-osmolarity environment by the insertion of element IS10 into the promoter of the otsBA operon, rewiring expression from RpoS dependent to RpoS independent. We wished to determine how the presence of IS10 in the genome of this strain shaped the evolutionary outcome. IS10 could influence the outcome by causing mutations that confer adaptive phenotypes that cannot be achieved by strains without the element. Alternatively, IS10 could influence evolution by increasing the rate of appearance of certain classes of beneficial mutations even if they are no better than those that could be achieved by a strain without the element. We found that populations evolved from an IS10-free strain did not upregulate otsBA. An otsBA-lacZY fusion facilitated the recovery of a number of mutations that upregulate otsB without involving IS10 and found that two caused greater fitness increases than IS10 insertion, implying that evolution could have upregulated otsBA in the IS10-free strain. Finally, we demonstrate that there is epistasis between the IS10 insertion into the otsBA promoter and the other adaptive mutations, implying that introduction of IS10 into the otsBA promoter may alter the trajectory of adaptive evolution. We conclude that IS10 exerts its effect not by creating adaptive phenotypes that could not otherwise occur but by increasing the rate of appearance of certain adaptive mutations.
PUBLISHED
published online 17 April 2010
Keywords: Microbiology; Escherichia coli; Genes & Society; Immunology, Inflammation & Infection